Penggunaan Komunikasi Simbolik Tentang Pilpres 2024 Pada Media Sosial X - Aslam, Muhammad; Andung, Petrus Ana; Pietriani, I Gusti Ayu Rina (Jurnal Riset Komunikasi, 2024)
The 2024 Presidential Election in Indonesia presents a number of candidate pairs who are trying to capture public attention through various strategies, including intensive political communication on social media. One of the candidate pairs that has attracted public attention is Anies Baswedan and Muhaimin Iskandar, or often abbreviated as "Paslon Anies-Cak Imin." This type of research is qualitative using the Cyber Media Analysis method. Methodologically, Cyber Media Analysis (AMS) is another variant of research based on netnography or virtual ethnography. Each level of analysis in AMS will provide the conditions of virtual communities on the internet. The use of symbolic communication about the 2024 Presidential Election on social media X for Candidate Pair No. 1 was found as an expression to communicate the figure and character of Anies as an ideal leader for the Indonesian Nation.